Enhancing Industrial Production Quality Through Innovations and System Improvements in Paving Block Manufacturing - Rahmawati Cut (Universitas Lancang Kuning, 2023)
The paving block industry in Aceh Besar District has experienced significant growth, leading to intensified competition among industry players. Thus, it is essential to introduce innovations in product development and operational procedures within the paving block industry to address this challenge. This community service initiative empowers partners to enhance their production systems and elevate the quality of their paving block products. The approach includes training on production procedures, guidance on standard paving block manufacturing protocols, and support in refining marketing techniques. As part of this initiative, partners have incorporated glass waste as a partial replacement for natural sand in their paving block products. This community service have demonstrated positive results, including increased sales production and improved knowledge of the paving block manufacturing process among partners. The sales volume of partner products has notably risen, with production reaching 5,720 and 8,920 units in January and May, respectively. Moreover, partners have observed sustained profit growth, experiencing a significant increase of 57.35%. These findings underscore the success of integrating glass waste as an alternative material, enabling partners to reduce production costs while maintaining product quality